Susceptibility to Oxidation of Selected Freshwater Fish Species Lipids as a Potential Source of Fish Oil in Dietary Supplements. (20th August 2021) - Tokarczyk, Grzegorz; Bienkiewicz, Grzegorz; Biernacka, Patrycja
Abstract : Polyunsaturated fatty acids from the omega 3 family are more and more often supplied to the diet in the form of supplements. The aim of the study was to characterize the lipid fractions of predatory freshwater fish, i.e., pike ( Esox lucius L.), perch ( Perca fluviatilis L.), and pike perch ( Sander lucioperca L.), and omnivorous fish, i.e., bream ( Abramis brama L.) and roach ( Rutilus rutilus L.). Their technological usefulness in terms of the source of fish oil was determined, depending on the rate and degree of their oxidative changes. UV radiation (photooxidation test) was used as a factor accelerating lipid oxidation. Research has shown that selected species of freshwater fish are characterized by high lipid oxidative stability, due to the availability and speed of delivery to the processing plant. The initial level of lipid oxidation of their meat, expressed by the TOTOX index, in any species did not exceed the value of 7, while the acceptable value was 26. The oil obtained from the meat of omnivorous fish after the photooxidation process was characterized by significantly better oxidative stability compared to the oil from the meat of predatory fish. The oxidation resistance of omnivorous fish oil was shown to be higher than that of predatory fish.